(untitled) (Building a culture in research ethics, bioethics and scientific integrity, 2024)
Philosopher, MG Analysis of contemporary political, economic, and international problems, MG Sociology of public action, MG Comparative research on development. Advisor to the Science Directorate of the Ministry of Science, Technology, and Innovation Ministry - Minciencias.